2010
DOI: 10.1007/s10658-009-9575-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of non-chemical seed treatment methods for the control of Alternaria dauci and A. radicina on carrot seeds

Abstract: The current study was initiated to evaluate the efficacy of physical methods (hot water, aerated steam, electron treatment) and agents of natural origin (resistance inducers, plant derived products, microorganisms) as seed treatments of carrots for control of Alternaria dauci and A. radicina. Control of both Alternaria species by seed treatment with the resistance inducers was generally poor. Results were also Eur J Plant Pathol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 23 publications
4
56
1
Order By: Relevance
“…Indeed, some of the treatments increased germination with respect to noninoculated non-treated seeds. Although similar results have been reported previously (Khan and Kumar, 1993;Souza et al, 2002;Brand et al, 2007;Koch et al, 2010;Steffen et al, 2010;Wulff et al, 2011), essential oils do not always exert a positive effect on seed quality. For example, the oils from Cinnamomum zeylanicum (Alves et al, 2004;Van der Wolf et al, 2008), Eucalyptus citriodora (Batish et al, 2004), and Agastache rugosa (Kim, 2008) inhibited, to varying extents, seed germination and seedling development.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, some of the treatments increased germination with respect to noninoculated non-treated seeds. Although similar results have been reported previously (Khan and Kumar, 1993;Souza et al, 2002;Brand et al, 2007;Koch et al, 2010;Steffen et al, 2010;Wulff et al, 2011), essential oils do not always exert a positive effect on seed quality. For example, the oils from Cinnamomum zeylanicum (Alves et al, 2004;Van der Wolf et al, 2008), Eucalyptus citriodora (Batish et al, 2004), and Agastache rugosa (Kim, 2008) inhibited, to varying extents, seed germination and seedling development.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, treatment of batches of potentially infected seeds with biocides prior to cultivation is more economical, reasonably efficient and commonly employed to control the dissemination of phytopathogens in the field (Machado, 2000). Various natural plant products are known to be effective against seed-associated pathogens Atanda et al, 2007;Brand et al, 2007;Slusarenko et al, 2008;Dhingra et al, 2009;Koch et al, 2010;Steffen et al, 2010), while the essential oils from the traditional Brazilian medicinal plants "hortelã do campo" [Hyptis marrubioides (Lamiaceae)], "alfazema-do-Brasil" [Aloysia gratissima (Verbenaceae)] and "erva-baleeira" [Cordia verbenacea (Boraginaceae)] have been shown to be effective in the control of Asian soybean rust (Silva et al, 2012a,b). In this context, we have investigated the effect of essential oils from these medicinal plant species on C. truncatum-infected seeds and, ultimately, on the control of anthracnose under greenhouse conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some experiments revealed that thyme oil may be effectively used also to control Alternaria spp. on carrot seeds [Dorna et al 2008, Koch et al 2010, Riccioni and Orzali 2011, Lopez-Reyes et al 2016. Properties of fir oil are less known, however its chemical composition may indicate antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…increased vacuolization of the cytoplasm and accumulation of lipid bodies, undulations of the plasmalemma, and alterations of the mitochondria and endoplasmic reticulum. Several authors confirmed that thyme oil may completely inhibit or significantly limit growth of fungal plant pathogens [Zambonelli et al 1996, Daferera et al 2003, Dorna et al 2008, Barrera-Necha et al 2009, Koch et al 2010, Riccioni and Orzali 2011, Lopez-Reyes et al 2016.…”
Section: Introductionmentioning
confidence: 93%
“…radicina . In addition, the effect of hot water treatment was signi fi cantly improved, when combined with either of the bacterial or fungal biocontrol agents (Koch et al 2010 ) . Application of the biofumigant fungus Muscodor albus treatment of wheat seeds effectively protected the plants against wheat common bunt disease caused by Tilletia caries (Goates and Mercier 2011 ) .…”
Section: Production Of Propagative Plant Materials Free Of Fungal Andmentioning
confidence: 99%